Peran Komunikasi Kesehatan dalam Mencegah Stunting di Kelurahan Laweyan - Muhammad Fauzi Sulaiman Hanafi; Sidiq Setyawan (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2026)
The purpose of the research is to analyze the contribution of health communication toward public awareness and behavioral change in stunting prevention in Laweyan Sub-District. The focus of the research will be oriented toward the change in knowledge, attitude, and practice on balanced nutrition, accounting consumption of junk food. The study applied a qualitative case study design that included respondents who were health officers, posyandu cadres, community leaders, and households of beneficiaries. Data were collected through in-depth interviews and observations, and documentation. Thematic analysis was used for data analysis. The results showed that health communication strategies in Laweyan used face-to-face counseling, digital media, and innovatively, Secating and Dasyat as the programs that increase the community understanding of balanced nutrition. However, effectiveness was reduced by low awareness of nutrition (about 45% of respondents did not consider themselves to have heard of balanced nutrition), lack of time by community members to attend counseling events, and lack of communication facilities at the sub-district level. Thus, more participatory communication strategies are required that involve local opinion leaders and strengthen community-based communication media for health messages that are easier to accept and apply to their daily lives.